Once Upon a Christmas Cheery in the Lab of Shakhashiri - Shakhashiri, Bassam Z. (1986)
One of many in a series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. The 1986 demonstrations focus on the science behind common kitchen and household products, like soap bubbles following Bernoulli's principle, combustion of various chemicals, color changing reactions, the pH of common kitchen and household products, nitric acid and copper, chemiluminescence, and creating polyurethane foam. Special guests include University of Wisconsin Chemistry professor Fred Juergens and Santa Claus. This video was taken from a DVD, which itself was made from an unknown magnetic tape. Any distortions in the image and sound of the video are inherent in the DVD itself and the audio of the 1986 lecture is particularly quiet.
Keywords: Science--Study and teaching; Lectures; Chemistry--Experiments; Christmas; Combustion; Educational films; Santa Claus (Fictitious character); Chemiluminescence